2000
DOI: 10.1007/s003830050021
|View full text |Cite
|
Sign up to set email alerts
|

Transverse testicular ectopia: preoperative diagnosis by ultrasonography

Abstract: Transverse testicular ectopia (TTE) is a rare anomaly. We report the first case of TTE described in Taiwan. The physical examination, ultrasonography (US), and laparoscopy revealed both testes in the left hemiscrotum, and surgical correction was performed. This case was diagnosed preoperatively by US, which can offer an easy, safe, and convenient alternative in the preoperative diagnosis of TTE. The possible mechanism for this anomaly and the literature are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…The first case was described in 1886 by Lenhossek [2]. Chen et al [3] reported the first Taiwanese case in 2000. The only case reported so far from Africa was from Nairobi, Kenya [4].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The first case was described in 1886 by Lenhossek [2]. Chen et al [3] reported the first Taiwanese case in 2000. The only case reported so far from Africa was from Nairobi, Kenya [4].…”
Section: Discussionmentioning
confidence: 98%
“…This is often obscured by the presence of a hernia on the affected side. Some cases, however, have been diagnosed radiologically by means of ultrasonography [3,8] and magnetic resonance imaging [9] and at laparoscopy [10,11] for the localisation of the undescended testis. In most of West Africa, surgical exploration remains the only tool for localising the undescended testis.…”
Section: Discussionmentioning
confidence: 98%
“…US and MRI can be used for preoperative diagnosis [9]. Before the increased use of laparoscopy, CTE was mostly diagnosed during hernia repair and inguinal exploration with the absence of the contralateral testis.…”
Section: Discussionmentioning
confidence: 99%
“…Le diagnostic est port6, le plus souvent, en per-op~ratoire au cours d'une cure d'hernie inguinale (41%) [6]. La d~couverte du testicule ectopique se fait de plus en plus en pr~op~ratoire par ~chographie, IRM pelvienne, angio-IRM, ou par laparoscopie diagnostique qui repr~sente, actuellement, la technique de rdf~rence dans i'exploration des testicules non descendus non palpables [2][3][4]10].…”
Section: Observationunclassified